Sensitivity and specificity of the Eating Assessment Tool and the Volume‐Viscosity Swallow Test for clinical evaluation of oropharyngeal dysphagia - Rofes, L.; Arreola, V.; Mukherjee, R.; Clavé, P. (Neurogastroenterology and motility, 2014)
Background Oropharyngeal dysphagia (OD) is an underdiagnosed digestive disorder that causes severe nutritional and respiratory complications. Our aim was to determine the accuracy of the Eating Assessment Tool (EAT‐10) and the Volume‐Viscosity Swallow Test (V‐VST) for clinical evaluation of OD. Methods We studied 120 patients with swallowing difficulties and 14 healthy subjects. OD was evaluated by the 10‐item screening questionnaire EAT‐10 and the bedside method V‐VST, videofluoroscopy (VFS) being the reference standard. The V‐VST is an effort test that uses boluses of different volumes and viscosities to identify clinical signs of impaired efficacy (impaired labial seal, piecemeal deglutition, and residue) and impaired safety of swallow (cough, voice changes, and oxygen desaturation ≥3%). Discriminating ability was assessed by the AUC of the ROC curve and sensitivity and specificity values. Key Results According to VFS, prevalence of OD was 87%, 75.6% with impaired efficacy and 80.9% with impaired safety of swallow including 17.6% aspirations. The EAT‐10 showed a ROC AUC of 0.89 for OD with an optimal cut‐off at 2 (0.89 sensitivity and 0.82 specificity). The V‐VST showed 0.94 sensitivity and 0.88 specificity for OD, 0.79 sensitivity and 0.75 specificity for impaired efficacy, 0.87 sensitivity and 0.81 specificity for impaired safety, and 0.91 sensitivity and 0.28 specificity for aspirations. Conclusions & Inferences Clinical methods for screening (EAT‐10) and assessment (V‐VST) of OD offer excellent psychometric proprieties that allow adequate management of OD. Their universal application among at‐risk populations will improve the identification of patients with OD at risk for malnutrition and aspiration pneumonia. Despite its high prevalence and severe complications, oropharyngeal dysphagia (OD) is not always systematically explored and detected, and most patients are not even diagnosed and do not receive any treatment for this condition. Videofluoroscopy (VFS) is the gold standard to OD diagnosis, however, it is not feasible to perform a VFS on every patient at risk for OD. The screening method Eating Assessment Tool (EAT‐10) and the clinical bedside method, Volume‐Viscosity Swallow Test (V‐VST) offer high accuracy for detecting OD.